2021
DOI: 10.1186/s43141-021-00115-4
|View full text |Cite
|
Sign up to set email alerts
|

Thidiazuron-induced direct organogenesis from immature inflorescence of three date palm cultivars

Abstract: Background Inflorescence explants of date palm proved to be a promising tool for micropropagation of elite cultivars or rare males and females as organogenesis and somatic embryogenesis could be achieved. These plant materials are abundantly available every year and can be used as cheap and potent explants. Nevertheless, many difficulties could be faced in this protocol according to selection of the spathe size and age, media components, growth regulators, etc. The aim of this study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Kuo and Xu reported similar outcomes in species Sinningia speciosa [13,16]. TDZ is considered as optimal synthetic cytokinin for the regeneration of many plant systems [17][18][19]. In our study, abundant and dwarf shoots were induced in MS medium containing TDZ, but, even prolonging the culture time, the differentiated adventitious buds failed to elongate (Figure 2F).…”
Section: Effect Of Pgrssupporting
confidence: 78%
“…Kuo and Xu reported similar outcomes in species Sinningia speciosa [13,16]. TDZ is considered as optimal synthetic cytokinin for the regeneration of many plant systems [17][18][19]. In our study, abundant and dwarf shoots were induced in MS medium containing TDZ, but, even prolonging the culture time, the differentiated adventitious buds failed to elongate (Figure 2F).…”
Section: Effect Of Pgrssupporting
confidence: 78%
“…Interestingly, we are the first to report the synergistic effects of BA and TDZ in protoplast culture. These results agree with various researchers who found that using BA together with TDZ can enhance the efficiency of cell development and regeneration of cells and tissues in other systems (Guo et al 2011;Jonoubi et al 2004;Khalafalla and Hattori 1999;Nielsen et al 1995;Taha et al 2021;Tantasawat et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…However, compared to the control treatment, a cross-talk between auxin and cytokinin is crucial for CI and MCI since the treatments without TDZ or IBA in the medium were not morphogenic, although some had produced callus. Previous studies have well documented that TDZ has effectively stimulated de novo morphogenesis in many recalcitrant plant species, such as Phoenix dactylifera [ 18 ], Cocos nuciera [ 19 ], etc. The cross-talk of TDZ × IBA could strongly trigger cell proliferation and de novo morphogenesis in many plant species including in vitro recalcitrants, because TDZ act as a very stable CK-like substance in plant systems that effectively participates in CK metabolism and auxin translocation and accumulation in the plant [ 20 ], on the other hand, IBA is also a well-known potent auxin for cell differentiation and proliferation and is widely used in callogenesis, morphogenic callus induction, and rooting events in most plant species, including the Ficus genus [ 4 , 7 ], as observed in the current study in F. lyrata .…”
Section: Discussionmentioning
confidence: 99%